2019
DOI: 10.3390/ijerph16193626
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Frailty Screening Instruments in the Emergency Department

Abstract: Early identification of frailty through targeted screening can facilitate the delivery of comprehensive geriatric assessment (CGA) and may improve outcomes for older inpatients. As several instruments are available, we aimed to investigate which is the most accurate and reliable in the Emergency Department (ED). We compared the ability of three validated, short, frailty screening instruments to identify frailty in a large University Hospital ED. Consecutive patients aged ≥70 attending ED were screened using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
92
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 51 publications
4
92
0
1
Order By: Relevance
“…The CFS has the highest specificity and accuracy; this test would be useful in the diagnosis but has low sensitivity compared with the other screening tests. This outcome is similar to a study that used the CFS compared with comprehensive geriatric assessment in the emergency department in the West of Ireland and found that the CFS has the following: sensitivity 51%, specificity 94%, PPV 93%, and NPV 57% when using the cut point of frailty at ≥ 5 [ 42 ]. A study that compared CFS screening and the Edmonton Frail Scale in the perioperative department of the Royal Melbourne Hospital revealed that the CFS has a sensitivity of 80.8% and specificity of 88.6% when using a CFS at ≥ 5 and that the area under the receiver operating characteristic curve was 0.91 (95% CI, 0.86 to 0.94) [ 43 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The CFS has the highest specificity and accuracy; this test would be useful in the diagnosis but has low sensitivity compared with the other screening tests. This outcome is similar to a study that used the CFS compared with comprehensive geriatric assessment in the emergency department in the West of Ireland and found that the CFS has the following: sensitivity 51%, specificity 94%, PPV 93%, and NPV 57% when using the cut point of frailty at ≥ 5 [ 42 ]. A study that compared CFS screening and the Edmonton Frail Scale in the perioperative department of the Royal Melbourne Hospital revealed that the CFS has a sensitivity of 80.8% and specificity of 88.6% when using a CFS at ≥ 5 and that the area under the receiver operating characteristic curve was 0.91 (95% CI, 0.86 to 0.94) [ 43 ].…”
Section: Discussionsupporting
confidence: 84%
“…The comparison of PRISMA-7 and the Fried phenotype (CHS criteria) showed the following: sensitivity 76%, specificity 86.24%, PPV 42.22%, NPV 96.45%, LR+ 5.22, LR- 0.28, and accuracy 85.05%. A study showed the PRISMA-7 compared with a comprehensive geriatric assessment in the emergency department in the West of Ireland and demonstrated that it has the following: sensitivity 84%, specificity 78%, PPV 84%, and NPV 78% when using PRISMA-7 score ≥3 [ 42 ]. A study in community-dwelling elderly individuals living in Antalya, Turkey, used PRISMA-7 compared with CFS and found that PRISMA-7 has the following: sensitivity 87.7%, specificity 76.5%, PPV 74%, and NPV 89% when using a cut-point ≥ 3 [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The severity of prior frailty at the time of admission is a prognostic indicator of outcome (length of stay, institutionalisation, and mortality) from acute medical and surgical illness [ 7 , 8 , 9 , 10 ]. Holistic medical management uses information from many sources, one of which is a frailty scale.…”
Section: Discussionmentioning
confidence: 99%
“…The Clinical Frailty Scale (CFS) developed by Rockwood et al in 2005 14 . While it was originally introduced to assess frailty in the context of the Canadian Study of Health and Aging, a five-year prospective study designed to assess the overall fitness and frailty of older individuals, it rapidly became a widely used instrument in clinical settings 15 . Its initial seven point scale, which later progressed to a ninepoint scale, categorizes individuals according to their level of robustness, activity levels and dependence to others.…”
Section: Overall Frailty Scores/toolsmentioning
confidence: 99%